Assessment of the Marketing Activity in Five-Star Hotels - Farghaly, Ibrahim Sedeek; Soliman, Sherif Gamal Saad (جامعة المنصورة - كلية السياحة والفنادق, 2017)
This study aims to assess the marketing activitiy in five star hotels in Greater Cairo. It identifies the factors that have an impact on customers' purchasing decisions. A questionnaire form was developed to collect the required data for this study. A total of 300 forms were randomly distributed to a sample of hotel guests; only 248 forms (82.7%) were valid for analysis. Moreover, 20 valid forms were received from marketing managers. The obtained results showed that the majority of marketing managers use face to face selling as a direct marketing, in addition to the demand based pricing, they organize celebrations of different events and they continuously update the hotels’ offers and discounts. On the other hand, the majority of the surveyed guests showed interest in offers and discounts provided by hotels; they prefer hotels that offer fair prices and ensure quality of service. In general, they use travel agents, hotels advertising campaigns and the internet for searching and they use the internet heavily to help them make travel decisions more quickly.
النشاط التسويقي الناجح هو الذي يخلق الاتصال المستمر بين رجل التسويق والعملاء سواء كان بطريقة مباشرة أو غير مباشرة. تسعي هذه الورقة البحثية إلى تقييم النشاط التسويقي بفنادق الخمس نجوم بالقاهرة الكبرى ومعرفة العوامل التي تؤثر على القرار الشرائي لدي العملاء. تم توزيع استمارات استبيان بطريقة عشوائية على مجموعة من الضيوف ومدراء التسويق بفنادق الخمس نجوم بالقاهرة الكبرى بهدف تحقيق أهداف البحث، فتم توزيع عدد (300) استمارة استبيان على الضيوف وتم تجميع وتحليل (248) استمارة صالحة بنسبة (82.7%). وأيضا تم توزيع (20) استمارة استبيان على مديري التسويق وكانت جميعها صالحة للتحليل. أظهرت النتائج أن أغلبية مديري التسويق يفضلون البيع وجها كطريقة من طرق التسويق المباشر وأيضا يفضلون التسعير على حسب حجم الطلب وكذلك ينظمون الحفلات للمناسبات المختلفة لجذب العملاء وزيادة قوة العلاقة معهم وانتمائهم للفندق. تؤثر الأسعار المعتدلة على قرارات العملاء نحو اختيار الفنادق ثم العروض والخصومات ثم سهولة وسرعة عمليات الحجز، ثم تحديث معلومات الفندق باستمرار على موقعة الإلكتروني وكذلك صفحاته على مواقع التواصل الاجتماعي لمعرفة كل ما هو جديد عن الفندق. وذلك فلابد من اهتمام مديري التسويق بفنادق الخمس نجوم بتحسين وتطوير النشاط التسويق ومراعاة التطورات التكنولوجية ومواكبة العصر في حملاتهم الدعائية لتحقيق تطلعات العملاء وتحقيق رضاهم.
Keywords: الفنادق السياحية -- الحملات الدعائية -- مديرو التسويق -- رضا العملاء